STUDI PROSES BERPIKIR KRITIS MATEMATIS PESERTA DIDIK DALAM MEMECAHKAN MASALAH DITINJAU DARI GAYA BELAJAR DEPORTER DAN HERNACKI - Fuji Rianti; Aripin Aripin; Supratman Supratman (Universitas Halu Oleo, 2021)
This study aims to describe students' critical thinking process in solving problems in terms of DePorter and Hernacki's learning styles. This type of research includes qualitative research with exploratory research methods. The data collection method uses the think-aloud method. The research subjects were taken from class XI students of SMAN 1 Singaparna. The data analysis technique used was data reduction, data presentation and conclusion drawing. From the study results, it can be concluded that the critical thinking process: (1) visual students can pass the clarification and assessment stages well. However, at the inference and strategy stages, some students go through it well, and some cannot. Visual students use image media as visualization, link existing data to solve problems, have good writing skills and solve problems in a coherent, systematic, detailed and thorough manner. (2) auditorial students can pass the clarification and assessment stages well, but at the inference and strategy stages, some students pass it well and some who cannot. Auditorial students use prior knowledge constructs to solve problems, speak with a patterned rhythm, have difficulty writing but are good at speaking, are fluent speakers, and solve problems systematically but are less careful in doing calculations so that the answers they get are not correct. (3) Kinesthetic students can pass the clarification and assessment stages well. However, at the inference and strategy stages, some students go through it well, and some cannot pass it because they cannot understand the problem.